2018
DOI: 10.1002/ajmg.a.40351
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis III in Taiwan: Natural history, clinical and molecular characteristics of 28 patients diagnosed during a 21‐year period

Abstract: Mucopolysaccharidosis type III (MPS III, Sanfilippo syndrome) has a variable age of onset and variable rate of progression. However, information regarding the natural history of this disorder in Asian populations is limited. A retrospective analysis was carried out for 28 patients with MPS III (types IIIA [n = 3], IIIB [n = 23], and IIIC [n = 2]; 15 males and 13 females; median age, 8.2 years; age range, 2.7-26.5 years) seen in six medical centers in Taiwan from January 1996 through October 2017. The median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Somatic disease is relatively mild in Sanfilippo patients and consists typically of frequent ear-nose-throat infections, episodic diarrhea, hepatomegaly and/or splenomegaly, skeletal abnormalities, hirsutism, and coarse facies [11,[15][16][17][18][31][32][33][35][36][37][38][39][40]. At an early age, MPS III patients are typically taller with an increased head circumference compared to healthy children, but their growth slows around 5 years of age and by their late teens they are generally shorter than average [41].…”
Section: Neurobehavioral Abnormalities and Cognitive Decline As The Mmentioning
confidence: 99%
See 4 more Smart Citations
“…Somatic disease is relatively mild in Sanfilippo patients and consists typically of frequent ear-nose-throat infections, episodic diarrhea, hepatomegaly and/or splenomegaly, skeletal abnormalities, hirsutism, and coarse facies [11,[15][16][17][18][31][32][33][35][36][37][38][39][40]. At an early age, MPS III patients are typically taller with an increased head circumference compared to healthy children, but their growth slows around 5 years of age and by their late teens they are generally shorter than average [41].…”
Section: Neurobehavioral Abnormalities and Cognitive Decline As The Mmentioning
confidence: 99%
“…The main burden of the disease is the cognitive decline and associated behavioral problems. Indeed, the majority of patients first present with developmental (particularly speech) delay [11,[15][16][17][18][31][32][33][35][36][37][38][39][40]. In a study of 105 MPS IIIA, B, and C patients, the authors found that only 60 children acquired early language skills and that this acquisition was often later than 3 years of age [17].…”
Section: Neurobehavioral Abnormalities and Cognitive Decline As The Mmentioning
confidence: 99%
See 3 more Smart Citations